ANALISA KETIDAKEFEKTIFAN IDENTIFIKASI RISIKO MEMPENGARUHI PENILAIAN KINERJA PROYEK DI PT ALKHA INDUSTRI - Andi Martias; Rahma Wiyanti; Susan Rachmawati; Sudirja Sudirja (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
PT Alkha Industri (ALKAIND), as one of the leading industrial and design companies in Indonesia. Of course, handling projects worth hundreds of billions of rupiah and multi years requires a professional strategy and management so that the project is on time, does not exceed the costs that have been determined and in accordance with the specifications requested by the employer (client / owner). ALKIND already has project risk management rules/procedures and the project team has carried out project planning with risk management (risk identification). Research conducting analysis provides answers to the effectiveness of making project risk identification can affect the achievement of project targets. The data uses data from the company PT Alkha Industri from 2020 to 2022 for registered projects both completed and in progress. The results of the analysis can be concluded, 1) the risk owner who should identify potential risks in the project is not Project Control personnel because they do not know the potential risks of each function, 2) update risks every month by evaluating the realization of control, 3) risks so that their inherent risk score is reduced, 4) Perform other responses besides mitigating, namely how to avoid risk (avoiding), how to transfer risk (sharing / transferring), controlling risk (controlling) and optimizing risk (exploiting).